„Wszyscy wyszliśmy z wody” - Szczypiorska-Chrzanowska, Magdalena (Załącznik Kulturoznawczy, 2019)
This essay is an attempt of meditation over the phenomenon of photography, its philosophy and practice. Questions are put forward about the ontological status of the subject captured on the picture, about what is – and what might be – time in photography, what is a photographic moment, what is a photographic ‘reality’ and ‘fiction’. The starting point and the photo literary background of the essay is a juxtaposition of a daguerreotype from the literary fiction (from One Hundred Years of Solitude by Gabriel Garcia Marquez) and a daguerreotype from the real photography (Boulevard du Temple by Jacques Daguerre). Selected philosophical motifs analysed in works of Susan Sontag, François Soulages, Hans Belting, Roland Barthes, Edouard Pontremoli, Giorgio Agamben and Henri Cartier-Bresson make the context of the academic analysis.